Prioritary patents filed in Brazil and protected by the Patent Cooperation Treaty (PCT) route - Scartassini, Verônica Barboza (2020)
Introduction: the importance of a patent is recognized both at informational as well as in economic terms. The Patent Cooperation Treaty (PCT) is a way of extending patent filing protection and it is based on it that this study is consolidated. Objectives: this is a patentometric analysis done via a quantitative-descriptive approach to understanding the deposit of Brazilian patents with extensions of deposits in the PCT based on the Derwent Innovation Index (DII). Method: it collects data in three stages. First, we searched for all patents deposited in Brazil from 2004 to 2019, resulting in 381.598 records, which formed our main corpus. From this corpus, the patents with priority registration in Brazil were extracted, resulting in 263.104 records. Finally, the extraction of the patents with priority deposit in Brazil with extension to the PCT route was carried out, resulting in 12.073 record. Results: from this result, we verified the main depositors via PCT, the temporality of the registries, and the classification of the patents. The main depositors are mostly multinational companies from the United States, China, Sweden, France, Japan, Germany and Italy, and universities, in the case of Brazil. The publications show oscillation in the stipulated period, keeping an average of 794 patents per year. The deposits are mainly concentrated in three major subareas: human necessities, performing operations and transporting, and electricity. Conclusions: it concludes that the extension of PCT protection is not a recurring practice by claimants who primarily deposit in the Brazilian territory